Analisis Strategi Promosi Terhadap Penjualan di Batik Mart - Iswarti Utami (LPPM-STPI, 2021)
Promotion is part of the marketing mix that cannot be separated from other parts and has an important and strategic role. A product needs to be socialized to consumers by using appropriate promotional strategies. The shift in consumer appetite from shopping off line (regular) to on line (interactive media) is a challenge that must be entered by business actors so that their business is in line with market and consumer wants. Promotion strategy analysis of sales is an analysis of the strategy implemented by a company. By using a comparative qualitative research method, the author tries to analyze the promotional strategies used by Batik Mart to attract consumer buying interest in order to get the expected sales. Limited promotional costs require Batik Mart management to use appropriate promotional strategies, up to date and according to the dynamic of the promotion itself. To compare the promotional programs analyzed for 4 months by comparing between promotional programs, the results of the research analysis can be seen as follows: Promotion for the period of 1 month January - February 2019, total sales of Rp. 188. 877,700, promotion period 2 months March - April 2019, total sales of Rp. 241,756,010, so there was an increase in sales of 27.99%.